The Effects of Cohesive Devices Used in the Background of the Study of English Department Students’ Undergraduate Theses - Ni Kadek Lestya Adnya Suari; I Nyoman Udayana; I Gusti Ngurah Parthama (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2022)
This study entitled The Effects of Cohesive Devices Used in the Background of the Study of English Department Students' Undergraduate Theses aims to analyse the effects of the overuse, underuse, and misuse cohesive devices employed by the English Department students in the background of the study in their undergraduate theses. The data of this study is taken from ten backgrounds of the studies written by the English Department students, Faculty of Humanities, Udayana University submitted in 2021 in various topic. This study is conducted using descriptive qualitative method. In collecting the data, documentation method utilized by a checklist instrument and note-taking technique are used to collect the data. The method for presenting the data analysis in this study could be formal and informal. In analysing the data, this study employs the theory from Halliday and Hassan (1976) about the cohesive devices and supporting theory by Ong (2011). The results of this study show that there are several types of cohesive devices are overused, underused, and misused. The overuse of cohesive devices is dominated by the overuse of repetition, conjunction, reference, and synonym. Then, the underuse of cohesive devices found in conjunction and reference. Lastly, the misuse of cohesive devices is found in reference and conjunction. The effects from these overuse, underuse, and misuse of cohesive devices affect the text, especially the connections of the ideas become not in cohesion. Those cases also affect the effectiveness, clarity, and the way the reader comprehend the meaning of the text.